Attitude and willingness of pediatric dentists regarding dental care for children with developmental and intellectual disabilities. (3rd December 2018) - Abraham, Simi; Yeroshalmi, Farhad; Margulis, Keith S.; Badner, Victor
Abstract: Aim: Children with developmental and/or intellectual disabilities (DD/ID) are considered to be at greater risk of developing dental disease and are more likely to have unmet dental needs than other children. The purpose of this study was to determine the attitude and willingness of pediatric dentists and residents to provide dental care for children with DD/ID. Methods: Two surveys were created and emailed via SurveyMonkey ® to pediatric dentists and post‐doctoral student members of the American Academy of Pediatric Dentistry. Results: Five hundred and seventy‐four pediatric dentists (9%) and 143 pediatric dentistry residents (13%) responded. Ninety‐nine percent of the practicing pediatric dentists do provide dental care for children with DD/ID. Ninety‐six percent of the practitioners are confident/very confident in treating these children with nonpharmacological methods, while 86% are confident/very confident with pharmacological methods. Among the residents, 99% are willing to provide dental care to children with DD/ID after they graduate. Eighty‐six percent of the residents are confident/very confident in treating these children with nonpharmacological methods, while 70% are confident/very confident with pharmacological methods. Conclusion: Pediatric dentist and resident respondents to the survey were overwhelmingly willing to provide dental care for patients with DD/ID and are confident with pharmacological and nonpharmacological treatment modalities.